Continued rise in rates of cardiovascular implantable electronic device infections in the United States: temporal trends and causative insights. - Voigt A; Shalaby A; Saba S (Pacing & Clinical Electrophysiology, 2010)
Background: Cardiovascular implantable electronic device (CIED) infections have been increasing out of proportion to the number of devices implanted, based on data available through 2003. We investigated recent trends and possible causes of the increasing numbers of CIED infections. Methods: We analyzed the occurrence of CIED infections and the associated changes in characteristics of CIED recipients, using the National Hospital Discharge Survey database from 1996 through 2006. Results: The number of CIED implantations continued to increase after 2003 from 199,516 in 2004 to 222,940 in 2006, representing a 12% increment. In the same period, the number of CIED infections increased from 8,273 in 2004 to 12,979 in 2006, representing a 57% increment. From 1996 to 2006, comorbid illnesses in recipients of new CIED devices became more prevalent with an increasing percentage of patients with end-organ failures (6.5% in 1996 vs 8.0% in 2006, P < 0.001) and diabetes mellitus (14.5% in 1996 vs 16.5% in 2006, P = 0.005). The proportion of Caucasian recipients also decreased (65.6% in 1996 vs 57.6% in 2006, P < 0.001). During that same period, the number of implanted cardiac resynchronization devices increased dramatically while the age of CIED recipients did not change. Conclusion: The number of patients with CIED-related infections in the United States continues to increase out of proportion to the increase in implantation rates. Possible causes for this on-going epidemic include sicker patients with varying racial backgrounds, and more complex procedures. These insights may help improve our ability to best select patients for CIED implantation in 'real-life' settings. (PACE 2010; 414-419)